Pengaruh Tingkat Perputaran Kas dan Perputaran Piutang Terhadap Profitabilitas Pada Lembaga Perkreditan Desa (LPD) di Kecamatan Payangan - Ningsih, Ni Kadek Vera; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to determine whether cash turnover and accounts receivable turnover affect profitability. This research uses causal quantitative research. Lembaga Perkreditan Desa (LPD) di Kecamatan Payangan, constitute the population in this study, there are 48 LPD. The total sample in this study was 33 LPD obtained using a purposive sampling technique. The types of data used are quantitative data, secondary data sources, and documentation data collection. Multiple linear regression analysis is the data analysis technique used. The results showed that (1) the level of cash turnover has a positive and significant effect on profitability. (2) accounts receivable turnover has a positive and significant effect on profitability. (3) the level of cash turnover and accounts receivable turnover simultaneously has a positive and significant effect on profitability. The higher the cash turnover, the cash that comes back through sales can be used to fund the company's operational activities. So that the financial condition of the LPD will always be protected and profitability will also increase. The higher the turnover of receivables from disbursed loans will be followed by an increase in profits from the disbursed credit interest thereby increasing profitability.